2003
DOI: 10.1002/gps.1002
|View full text |Cite
|
Sign up to set email alerts
|

Language impairment in dementia: impact on symptoms and care needs in residential homes

Abstract: Language disorders are associated with both behavioural and psychological symptoms of dementia even when severity of dementia is controlled for. Patients' needs in communication skills should be addressed earlier to help them maintain social interactions and reduce the impact on behavioural problems and patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 32 publications
(27 reference statements)
4
61
2
4
Order By: Relevance
“…Studies of communication in dementia care generally frame the issue in terms of verbal communication, and have delivered conflicting results. [3][4] For example, Potkins et al 3 suggested that caregivers should speak slowly and in short sentences, ask closed-ended questions, and talk about concrete matters. Small et al, 4 in contrast, argues that slower speech is ineffective as persons with dementia forget the earlier part of the utterance, and that too much verbal communication and too many demands made by caregivers might be challenging for the persons with dementia, and thereby lead to problematic behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of communication in dementia care generally frame the issue in terms of verbal communication, and have delivered conflicting results. [3][4] For example, Potkins et al 3 suggested that caregivers should speak slowly and in short sentences, ask closed-ended questions, and talk about concrete matters. Small et al, 4 in contrast, argues that slower speech is ineffective as persons with dementia forget the earlier part of the utterance, and that too much verbal communication and too many demands made by caregivers might be challenging for the persons with dementia, and thereby lead to problematic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of communication in dementia care generally frame the issue in terms of verbal communication only. [3][4] What is lacking is a study designed to specifically examine both verbal and nonverbal communication between PWDs and their caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…49 O distúrbio de linguagem em idosos com DA tem sido associado com o desenvolvimento de problemas comportamentais e sintomas psicológicos significativos. 50 Com a evolução da doença, os cuidadores familiares não sabem quais estratégias de comunicação funcionam melhor, apesar de sua maior experiência e exposição aos problemas. O estudo de Savundranayagam et al, 48 No estudo em que foi investigada a associação entre alta expressão da emoção (que se refere à atitude crítica ou hostil do cuidador) e problemas comportamentais, os resultados indicaram que a alta expressão da emoção pelo cuidador foi associada com níveis mais elevados de hiperatividade do paciente, senso de menor competência do cuidador e maior chance de institucionalização.…”
Section: A Relação Entre O Cuidador E Os Sintomas Neuropsiquiátricos unclassified
“…As a matter of fact, NPH patients reveal a fact that language disorders (receptive and expressive) are correlated with both behavioral and psychological symptoms of dementia. This relationship remains fixed even when the severity of dementia is controlled (Dawn et al, 2003;Spronk et al, 2003;Potkins et al, 2003;Prodan et al, 2009). …”
Section: Types Of Scdmentioning
confidence: 99%